Hubungan Iran-Amerika Serikat Masa Pemerintahan Hassan Rouhani (Telaah Perjanjian JCPOA) - Alkholid, Ayu Maulida; Taufiq, Firmanda (Journal Of Middle East and Islamic Studies, 2021)
Relations between Iran and the United States show fluctuating dynamics. The historical relationship and cooperation between the two countries represents how the process works. In fact, during the reign of Shah Reza Pahlavi, Iran-US relations looked good and established important cooperation in several sectors. The political constellation of Iran that continues to intertwine makes the US also respond and issue various policies, including the issue of the nuclear development program. The program during the reign of Hassan Rouhani was also one of the priority policies. Until, the JCPOA agreement was formed between Iran and the P5+1 group countries (US, UK, France, Russia, China, and Germany). However, in 2015, the US tried to get out of the agreement because the contents of the agreement did not match the views of US domestic policy. Political constellations and the process of nuclear development are important discourses in viewing the relationship that is being built between Iran and the US. This article seeks to examine the dynamics of relations and cooperation between Iran and the US during the reign of Hassan Rouhani, the reasons for the US leaving the JCPOA agreement, and the background of Iran continuing its nuclear development. The data collection method that the researcher uses is by collecting various references, both from books, journals, newspapers, online media, and other literature related to the issue of relations and cooperation between Iran and the US during the Hassan Rouhani administration and topics surrounding the cause of the US leaving the JCPOA agreement.